TINDAK TUTUR DIREKTIF DALAM SERIAL MAK BETI - Zulfa, Ilma (University of Brawijaya, 2025)
The objectives of this study are 1) Knowing the forms of directive speech acts, 2) Knowing the function of directive speech acts, and 3) Knowing the strategy of delivering directive speech acts in the Mak Beti series episode Mak Beti Makan Hati karena Beti. The data used in this study are directive speech acts in the video series Mak Beti episode Mak Beti Makan Hati karena Beti, this video aired on October 25, 2024 and has aired 4.9 million times. Data analysis in this study uses three data analysis flows, namely 1). Data reduction, researchers reduced all the speech contained in the mak beti video series and selected directive speech acts, 2). Presentation of data, in presenting the data, the researcher presents based on the form and function of speech between the characters, 3). Conclusion drawing. The result of this research shows that there are at least 24 directive speech acts. The form and function of directive speech acts in Mak Beti's video are divided into 6, namely in the form of orders, requests, prohibitions, warnings, suggestions, and insistence. The strategies often used in the delivery of directive speech acts are direct, literal, and direct literal speech acts.